Evolutionary modification of development in mammalian teeth: Quantifying gene expression patterns and topography - Jernvall, Jukka (The National Academy of Sciences, 2000)
The study of mammalian evolution often relies on detailed analysis of dental morphology. For molecular patterning to play a role in dental evolution, gene expression differences should be linkable to corresponding morphological differences. Because teeth, like many other structures, are complex and evolution of new shapes usually involves subtle changes, we have developed topographic methods by using Geographic Information Systems. We investigated how genetic markers for epithelial signaling centers known as enamel knots are associated with evolutionary divergence of molar teeth in two rodent species, mouse and vole. Our analysis of expression patterns of Fgf4, Lef1, p21, and Shh genes in relation to digital elevation models of developing tooth shapes shows that molecular prepatterns predict the lateral cusp topography more than a day in advance. A heterotopic shift in the molecular prepatterns can be implicated in the evolution of mouse molar, changing locations from which historically homologous cusps form. The subtle but measurable heterotopic shifts may play a large role in the evolution of tooth cusp topographies. However, evolutionary increase in the number of longitudinal cusps in vole molar has involved accelerated longitudinal growth and iterative addition of new cusps without changes in lateral cusp topography. The iterative addition of cusps after the establishment of lateral cusp topography may limit the independence of individual morphological features used in evolutionary studies. The diversity of mammalian molar patterns may largely result from the heterotopic and iterative processes.